Are midsagittal tissue bridges predictive of outcome after cervical spinal cord injury?. Issue 5 (May 2017) - Huber, Eveline; Lachappelle, Patrice; Sutter, Reto; Curt, Armin; Freund, Patrick
Abstract : T2 ‐weighted scans provided data on the extent and dynamics of neuronal tissue damage and midsagittal tissue bridges at the epicenter of traumatic cervical spinal cord lesions in 24 subacute tetraplegic patients. At 1 month postinjury, smaller lesion area and midsagittal tissue bridges identified those patients with lower extremity evoked potentials and better clinical recovery. Wider midsagittal tissue bridges and smaller lesions at 1 month post‐injury were associated with neurological and functional recovery at 1‐year follow‐up. Neuroimaging biomarkers of lesion size and midsagittal tissue bridges are potential outcome predictors and patient stratifiers in both subacute and chronic clinical trials. Ann Neurol 2017;81:740–748